2022
DOI: 10.3390/cancers14143306
|View full text |Cite
|
Sign up to set email alerts
|

Urine CA125 and HE4 for the Triage of Symptomatic Women with Suspected Endometrial Cancer

Abstract: A simple, noninvasive and accurate detection tool that can triage women with suspected endometrial cancer for definitive testing will transform patient care. The aim of this study was to evaluate urine CA125 and HE4 levels for the detection of endometrial cancer in symptomatic women. This was a cross-sectional diagnostic accuracy study of 153 symptomatic women who underwent urgent diagnostic investigations for suspected endometrial cancer at a large gynecological cancer center. Urine samples were collected pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…No studies have evaluated the serum markers in combination with endometrial thickness for endometrial cancer detection; however, urine CA125 and HE4 in combination with ET has been investigated, with a reported improvement in AUC with the addition of urine CA125 to ET compared with ET alone (AUC 0.97 vs. 0.94, respectively) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…No studies have evaluated the serum markers in combination with endometrial thickness for endometrial cancer detection; however, urine CA125 and HE4 in combination with ET has been investigated, with a reported improvement in AUC with the addition of urine CA125 to ET compared with ET alone (AUC 0.97 vs. 0.94, respectively) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Njoku et al [ 72 ] for the first time focused on the diagnostic accuracy of urine CA125 and HE4 levels for the triage of women with postmenopausal abnormal uterine bleeding. Overall, 153 women participated in the study and they were divided into two cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery cohort included 61 women (30 endometrial cancer cases and 31 controls). The validation cohort included 92 (33 cases and 59 controls) [ 72 ]. Urine samples were collected prior to any clinical procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TVS screening for endometrial cancer has good sensitivity in postmenopausal women, as shown by a case–control study within the United Kingdom Collaborative Trial of Ovarian Cancer Screening (UKCTOCS) cohort [ 20 ]. Recent studies have shown that urine CA125 displays potential as a diagnostic marker for symptomatic women with suspected endometrial cancer [ 21 ], but more robust molecular markers are still to be implemented in the clinical practice [ 22 ].…”
mentioning
confidence: 99%